Market Structure and Competition among Retail Depository Institutions - Cohen, Andrew M.; Mazzeo, Michael J. (The Review of Economics and Statistics, 2007)
We assess competition among retail depository institutions in 1,884 rural markets. We estimate an equilibrium market structure model that endogenizes the operating decisions of three types of depository institutions: multimarket banks, single-market banks, and thrift institutions. Observed market structures and a game-theoretic specification of entry behavior identify the parameters of an underlying profit function. We find strong evidence that product differentiation generates additional profits for retail depository institutions. These profits help to maintain smaller banks and thrifts, even as larger banks expand their operations. Consumers have more options, as more institutions can profitably operate as a result of product differentiation.